Critical success factors for e-learning in developing countries: A comparative analysis between ICT experts and faculty - Bhuasiri, Wannasiri; Xaymoungkhoun, Oudone; Zo, Hangjung; Rho, Jae Jeung; Ciganek, Andrew P. (Computers and education, 2012)
This study identifies the critical success factors that influence the acceptance of e-learning systems in developing countries. E-learning is a popular mode of delivering educational materials in higher education by universities throughout the world. This study identifies multiple factors that influence the success of e-learning systems from the literature and compares the relative importance among two stakeholder groups in developing countries, ICT experts and faculty. This study collected 76 usable responses using the Delphi method and Analytic Hierarchy Process (AHP) approach. The results reveal 6 dimensions and 20 critical success factors for e-learning systems in developing countries. Findings illustrate the importance of curriculum design for learning performance. Technology awareness, motivation, and changing learners’ behavior are prerequisites for successful e-learning implementations. Several recommendations are provided to aid the implementation of e-learning systems for developing countries which have relevance for researchers and practitioners. Limitations as well as possible research directions are also discussed. ► This study identifies the critical success factors of e-learning systems in developing countries. ► This study compares the success factors of e-learning between ICT experts and faculty. ► This study employed the Delphi method and AHP approach to identify success factors. ► The results show that there are 6 dimensions and 20 success factors for e-learning adoption in developing countries.